ROLE OF MULTINATIONAL CORPORATION AND SHARE OF THEIR INVESTMENT IN PRIORITY SECTORS OF ECONOMY OF RK (ҚазҰУ хабаршысы. Экономика сериясы, 2019)
Kazakhstan is the leader in attraction of foreign investments among is central the Asian countries. Today multinational corporations – the main tool in business expansion internationally. This article is devoted to studying of activity of the main participants of process of globalization of economy – multinational corporations in Kazakhstan. Authors considered the main directions and volumes of streams of direct foreign investments to the country in recent years. Key indicators of PII in the country and the prospects of development are defined. In article major factors of attraction of direct foreign investments are studied. The review of scientific literature on the factors defining inflow of direct foreign investments to Kazakhstan is made. Results showed that, despite existence of various motives in adoption of investment decisions by multinational corporations, direct foreign investments to Kazakhstan are generally sent to the raw sector of economy. In article the analysis of inflow of direct foreign investments in a section from 2014 to 2019, is carried out to priority sectors of economy of the Republic of Kazakhstan which mining industry, processing industry, professionally scientific and technical activity and innovative development are. In work questions of investment into priority sectors of economy of RK were investigated. Analytical also statistical methods, a dialectic method of knowledge and observation formed a methodological basis of a research. The main volume of foreign investments still goes to the spheres which are not demanding large-scale investments and characterized by fast payback. Thus, drawing a conclusion on a research of trends of functioning, outflow and inflow of direct foreign investments on priority sectors of economy of the Republic of Kazakhstan, in industry structure of investments, the main share is occupied by the mining industry, and the oil and gas industries still are on one of the first places on the level of the involved investments. Such industries as construction and manufacturing industry receive the smallest number of foreign investments. Article has the scientific value and novelty of a research where relevance of work is application of an integrated approach to a research of the international investment activities and a role transnational corporation, in identification of the internal and external regularities defining the direction and dynamics of investment activities in the Republic of Kazakhstan.